Evaluación de Collect Earth como herramienta para estimar datos de activiada para el sistema de medición, reporte y verificación del programa de REDD+ en Costa Rica. - Romero-Badilla, David Alonso (Instituto Tecnológico de Costa Rica, 2018)
This study examines the capacity of the software Collect Earth to generate activity data as required by Costa Rica’s REDD+ MRV system. Thereby, consistency of Collect Earth data obtained for the 2013-2015 period in Costa Rica was evaluated, and estimations of land use and land use changes for the cycle 2014-2015 were made. The data was obtained by 14 different interpreters through Multitemporal Visual Interpretation of sampling points using high resolution satellite imagery. To evaluate data consistency between interpreters a second land use interpretation was made on a subsample of the data. Variability between land use interpretations was assessed through a paired-sample t test, and confusion matrices. Using previously collected data for the 2014-2015 period, estimations about areas of change were made according to general REDD+ land use change categories and REDD+CR activities categories. Evaluation of two different types of stratifications were also made. Results show data global consistency was 73 and 69 % for 2013 and 2015 respectively. The main source of disagreements between interpreters was the confusions among the subcategories of forestry lands and other closely related categories. The study demonstrates that it is possible to estimate activity data following the REDD+ CR MRV system’s designed approaches using Collect Earth. However, it is necessary to intensify the sampling in areas of interest in order to reduce uncertainties.
Tesis de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2018.
Keywords: Imágenes de satélite; Uso de la tierra; Deforestación; Datos; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Soil science::Soil physics